List context effects in languages with opaque and transparent orthographies: a challenge for models of reading - Traficante, Daniela; Burani, Cristina (Frontiers in Psychology, 2014)
This paper offers a review of data which show that reading is a flexible and dynamic process and that readers can exert strategic control over it. Two main hypotheses on the control of reading processes have been suggested: the route de-emphasis hypothesis and the time-criterion hypothesis. According to the former, the presence of irregular words in the list might lead to an attenuation of the non-lexical process, while the presence of non-words could trigger a de-emphasis of the lexical route. An alternative account is proposed by the time-criterion hypothesis whereby the reader sets a flexible deadline to initiate the response. According to the latter view, it is the average pronunciation difficulty of the items in the block that modulates the time-criterion for response. However, it is worth noting that the list composition has been shown to exert different effects in transparent compared to opaque orthographies, as the consistency of spelling-sound correspondences can influence the processing costs of the non-lexical pathway. In transparent orthographies, the non-lexical route is not resource demanding and can successfully contribute to the pronunciation of regular words, thus its de-emphasis could not be as useful/necessary as in opaque orthographies. The complex patterns of results from the literature on list context effects are a challenge for computational models of reading which face the problem of simulating strategic control over reading processes. Different proposals suggest a modification of parameter setting in the non-lexical route or the implementation of a new module aimed at focusing attention on the output of the more convenient pathway. Simulation data and an assessment of the models’ fit to the behavioral results are presented and discussed to shed light on the role of the cognitive system when reading aloud.